The Role of Elijah Muhammad to Spread Islām in Modern America : an Analysis of his Efforts and Approaches - Gambari, Muhammad Aliyu; Hassan, Muhammad Kannike (International Journal of Islamic Khazanah, 2023)
Based on the available materials and literature, Islām got to America as far back as 1530 when the early African Muslim slaves were taken to the land of America. Elijah Muhammad was one of the Muslim who works and struggled hard on how Islam would be spread and progress in America. Later on, the Muslim Emigrants from various parts of the World also entered America around 19th Century. Hence, it's increasing the population and strengthening the growth of the religion of Islām in the area. The West particularly America known for her secularism, capitalism and extreme individualism with a political ideology not based on the recognition of the creator talk less of monotheism. From all indication, Islām continues to grow from strength to strength despite all odds in its way. Its therefore in the light of the above, the methodology adopted for this paper was historic and descriptive method in order to describe the nature of Islām in America and its practices among the black America and the emigrants during the early days of Islām. The paper concluded that Elijah Muhammad was a great revivalist, preacher and scholars in the spread of Islam in America. Islām equally penetrated in one way and the other into the nook and cranny of America through the peaceful preaching among the Muslim slaves and the people of America.